Relação entre o Desempenho no Processo Seletivo para Acesso ao Ensino Superior e o aproveitamento durante um curso de medicina - Ailton Paulo de Oliveira Júnior (Universidade Estadual Paulista Júlio de Mesquita Filho, 2012)
The study shows the correlation between the results obtained in the first selection process for 2003 conducted by the Universidade Católica de Brasilia for the medical school and the socio-demographic variables (gender, age, place of residence and place of birth) with the performance of students passed in the first three semesters. To this end, we validated the selection process for student enrollment in the course and determine if the result obtained in the selection process interferes with the performance of students in the course. Thus, the discriminating power of the tests of mathematics, biology and chemistry indicate that these evaluations are able to differentiate the candidates with the most ability of those who have a lower area of the contents and, therefore, reach the goal that is the ranking of the best candidates. It is concluded that influences the outcome of the contest vestibular and sociodemographic variables considered have become increasingly smaller over the course indicating that it is the dimension of academic achievement that assumes greater importance in explaining the performance of pupils